The Value of the Stay-green Traits with Grain Yield of Post Flowering Drought Tolerance in Rabi Sorghum - Kumar, D. Dev; Padma, V.; Talwar, H. S.; Jabeen, Farzana (International Journal of Bio-resource and Stress Management, 2021)
An experiment was conducted during rabi 2012-13 at research farm of Indian Institute of Millet Research (IIMR), Rajendranagar, Hyderabad, Telengana State, India. The experiment was laid out in a split plot design, replicated thrice, with 10 Sorghum genotypes as main treatment Well-watered (WW) and Water-stress (WS) conditions) to examine the potential of Sorghum genotypes to adapt to the post flowering drought. 10 genotypes are sub-treatments CRS 4, CRS 19, CRS 20, PEC 17, CSV 18, M 35-1, Phule chitra, Phule moulee, EP 57 and CRS 1). Among the four stages viz., 10, 20, 30 and 40 days after flowering (DAF), the GLAR (stay green trait) at 10 DAF had a positive and higher significant correlation with grain yield (r=0.66). So, GLAR at 10 DAF is most appropriate stage to screen for post flowering drought tolerance. Among the yield components, number of grains per panicle, grain weight panicle-1 and harvest index (HI) are significantly and positively correlated with grain yield and therefore it can be ascribed that the genotypes, which partitioned more assimilates into economic parts and in which grain filling is high, recorded more grain yield. The overall yield reduction due to moisture stress during the post flowering drought was 10% and it ranged between 8-12% among the genotypes. This indicates that the genotypes used in the present study are relatively drought tolerant. The genotypes CSV 18 and Phule moulee registered least yield reduction (8%) in grain yield due to post flowering drought followed by PEC 17 and M 35-1 which registered 9% yield reduction. However, the overall grain yield of PEC 17 and M 35-1 was more than CSV 18 and Phule moulee even under moisture stress conditions.